The first Pacific insular orchid bee (Hymenoptera, Apidae): A new species of Eufriesea from the Islas Marías - Ricardo Ayala; Victor H. Gonzalez; Michael S. Engel (Journal of Hymenoptera Research, 2022)
A new species of the orchid bee genus Eufriesea Cockerell (Apidae: Apinae: Euglossini) is described and figured from the Islas Marías of Nayarit State, México in the Pacific. Eufriesea insularis sp. nov., is a member of the coerulescens species group and is restricted to Islas Marias. The species is readily recognized by its dark blue integument with purple iridescence, black pubescence, dark wings, and clypeus green with purple hues and a prominent elevated ridge along the midline. The new species is known only from the female.